The impact of competition from venture capitalists on corporate venturing investment - Marco Bade (The Journal of Entrepreneurial Finance (JEF), 2020)
This study proposes a model on corporate venturing (CV) investment and examines the impact of venture capital (VC) activity in the economy on CV firms' investment. The presence of VCs creates competition for entrepreneurs. This reduces CV firms' expected venturing returns, and thus gives rise to a financial disincentive to CV investment. The empirical prediction of this result is that competition for talent should decrease CV investment. This prediction contradicts previous statements in the theoretical literature on CV.
Keywords: D86; G3; L26; M13; 650; Corporate venturing; Corporate venturing investment; Venture capital